Effectiveness of insecticide-impregnated dog collars in reducing incidence rate of canine visceral leishmaniasis: A systematic review and meta-analysis - Yimam, Yonas; Mohebali, Mehdi (PloS one, 2020)
Canines are proven reservoir hosts of Leishmania infantum, the causative agent of human zoonotic visceral leishmaniasis, and therefore domestic dogs play a central role in transmitting the disease to humans. Studies on the effect of insecticide-impregnated dog collars for controlling canine visceral leishmaniasis (CanL) have been increasing; however, meta-analysis has not been conducted. This study assessed the effectiveness of insecticide-impregnated dog collars for preventing CanL. We searched (PubMed, Web of Science, Scopus, Embase, Ovid Medline(R), and Cochrane library), from inception until 2 May 2020. Two authors independently performed articles screening and data extraction. We applied the RoB 2.0 tool to evaluate the risk of bias in randomized trials, while the ROBINS-I tool was used for non-randomized trials. I-squared statistics(I2) and funnel plot and Egger’s test, respectively, were used to assesses heterogeneity between studies and publication bias. Relative Risk (RR) and 95% Confidence Interval (CI) were calculated using the random-effects model in Stata 14 software. Out of 242 citations identified, 14 studies comprising 3786 collared dogs and 3428 uncollared dogs were eligible for meta-analysis. The use of deltamethrin-impregnated dog collars(DMC) showed an overall effectiveness of 54% (95%CI: 35–65%, I2 = 63.2%, P = 0.002) in decreasing incidence of CanL, while 10% imidacloprid and 4.5% flumethrin collars provided an overall effectiveness of 90% (95%CI: 80–96%, I2 = 0.0%, P = 0.376). DMC efficacy stratified by follow-up duration was estimated to be 58% (RR = 0.42, 95%CI: 0.20–0.87), 54% (RR = 0.46, 95%CI: 0.31–0.68), 53% (RR = 0.47, 95%CI: 0.29–0.82) for follow-up periods of 5 to 6 months, 1 year and 2 years, respectively. The current evidence indicates that using insecticide-impregnated dog collars can reduce the risk of CanL caused by L. infantum. Therefore, insecticide-impregnated dog collars could be a viable alternative for inclusion as a public health measure for controlling CanL.